Powder bed fusion of soft-magnetic iron-based alloys with high silicon content - Andreiev, Anatolii; Hoyer, Kay-Peter; Hengsbach, Florian; Haase, Michael; Tasche, Lennart; Duschik, Kristina; Schaper, Mirko (Journal of Materials Processing Technology)
Keywords: Industrial and Manufacturing Engineering; Metals and Alloys; Computer Science Applications; Modeling and Simulation; Ceramics and Composites

Mechanical joining of glass fibre reinforced polymer (GFRP) through an innovative solid self-piercing rivet - Han, Daxin; Yang, Keke; Meschut, Gerson (Journal of Materials Processing Technology)

Mechanical joining of glass fibre reinforced polymer (GFRP) through an innovative solid self-piercing rivet - Han, Daxin; Yang, Keke; Meschut, Gerson (Journal of Materials Processing Technology)
Keywords: Industrial and Manufacturing Engineering; Metals and Alloys; Computer Science Applications; Modeling and Simulation; Ceramics and Composites

Soft-magnetic behavior of laser beam melted FeSi3 alloy with graded cross-section - Andreiev, Anatolii; Hoyer, Kay-Peter; Dula, Dimitri; Hengsbach, Florian; Haase, Michael; Gierse, Jan; Zimmer, Detmar; Tröster, Thomas; Schaper, Mirko (Journal of Materials Processing Technology)

Friction-spinning—Grain structure modification and the impact on stress/strain behaviour - Lossen, Benjamin; Andreiev, Anatolii; Stolbchenko, Mykhailo; Homberg, Werner; Schaper, Mirko (Journal of Materials Processing Technology)

Joining with electrochemical support (ECUF): Cold pressure welding of copper - Ebbert, Christoph; Schmidt, H. C.; Rodman, D.; Nuernberger, F.; Homberg, W.; Maier, H. J.; Grundmeier, Guido (JOURNAL OF MATERIALS PROCESSING TECHNOLOGY)
Joining metals using electrochemical support (ECUF) is a new process for cold pressure welding sheets and parts. This new process is based on an electrochemical in-line surface treatment followed by incremental pilger rolling. The ECUF process intends to cold pressure weld materials under optimized conditions. Oxide layers on metal surfaces are known to inhibit the formation of cold pressure welds. The in-line electrochemical treatment will be used to remove these surface oxides for specific engineering metals and alloys. Hence, an improved pressure weld formation at lower forces and smaller reduction ratios is expected for the electrochemically treated surfaces. Using a more flexible pressure welding process, the number of applications could be greatly improved. First tests with copper were performed to analyse the efficiency of the proposed electrochemical surface treatments. Two electrochemical treatments, the cathodic oxide-reduction and cyclovoltammetric oxide-reduction, were compared with conventional treatments (degreasing and scratch brushing) regarding their influence on the cold pressure welding process of copper. The weld strength of lap welds has been investigated as well as the necessary reduction threshold to form a weld. It was found that the electrochemical oxide reduction resulted in higher weld strength. The results of scanning electron microscopy (SEM) and energy dispersive analysis of X-rays (EDX) indicate that surface oxides were successfully removed by the electrochemical surface treatments. (C) 2014 Elsevier B.V. All rights reserved.

Towards the multi-scale simulation of martensitic phase-transformations: An efficient post-processing approach applied to turning processes - Ostwald, Richard; Tiffe, Marcel; Bartel, Thorsten; Zabel, Andreas; Menzel, Andreas; Biermann, Dirk (Journal of Materials Processing Technology)